2003
DOI: 10.1038/nsb986
|View full text |Cite
|
Sign up to set email alerts
|

Myosin cleft movement and its coupling to actomyosin dissociation

Abstract: In recent years the structural basis of the actomyosin crossbridge cycle 1 has been defined in increasing detail by X-ray crystallography and electron microscopy 2-9 . 2 However, while crystal structures of myosin motor domains have been obtained for a number of nucleotide-bound states, the nature of the actin binding interaction has not been observed directly to date 2,3,8,10,11 . Residues involved in actin binding were identified by fitting the envelope of the myosin crystal structure into the electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 27 publications
5
91
1
Order By: Relevance
“…Other studies, using fluorescent probes flanking the 50 kDa cleft (Yengo et al 2002;Conibear et al 2003) and high-resolution cryo-electron microscopic maps of myosindecorated actin (Holmes et al 2003), confirmed that the cleft closes tightly when myosin binds strongly to actin and that this closure opens switch I. Kinesin and GTP-binding proteins have switch I in this open position (Vale 1996), but the open position of switch I had not been observed previously in myosin crystal structures. A study of binding of ATP analogues with large groups in place of the c-P i , though, had predicted its appearance (Pate et al 1997).…”
Section: Resurrection Of Schemementioning
confidence: 83%
“…Other studies, using fluorescent probes flanking the 50 kDa cleft (Yengo et al 2002;Conibear et al 2003) and high-resolution cryo-electron microscopic maps of myosindecorated actin (Holmes et al 2003), confirmed that the cleft closes tightly when myosin binds strongly to actin and that this closure opens switch I. Kinesin and GTP-binding proteins have switch I in this open position (Vale 1996), but the open position of switch I had not been observed previously in myosin crystal structures. A study of binding of ATP analogues with large groups in place of the c-P i , though, had predicted its appearance (Pate et al 1997).…”
Section: Resurrection Of Schemementioning
confidence: 83%
“…Because the nucleotide-binding pocket is located at the interface between the N-terminal and 50-kDa upper subdomains, the rotation of the 50-kDa upper subdomain necessarily opens up the pocket and is believed to lead to the subsequent release of ADP (3,6,34). Conversely, in the ATPbound state, the opening of the 50-kDa cleft (during which the 50-kDa upper subdomain rotates toward the N-terminal subdomain) is accompanied by the closing of the nucleotide-binding pocket (36).…”
Section: A Connection Between the 50-kda Upper And N-terminal Subdomamentioning
confidence: 99%
“…which make contact with a single actin subunit are structures which encircle a cleft in the 50 kDa fragment that is thought to undergo opening and closing motions [45]. In view of the importance of the description of both the nucleotide and actin-induced conformational changes in S1, it was decided to investigate these changes in solution at the strut location of the myosin head.…”
Section: Structural Studies Of Myosin S1mentioning
confidence: 99%